2019
DOI: 10.1590/0074-02760180347
|View full text |Cite
|
Sign up to set email alerts
|

The cost of a disease targeted for elimination in Brazil: the case of schistosomiasis mansoni

Abstract: BACKGROUND Schistosomiasis mansoni is a poverty-related parasitic infection that has a variety of clinical manifestations. We consider the disability and deaths caused by schistosomiasis unacceptable for a tool-ready disease. Its condition in Brazil warrants an analysis that will enable better understanding of the local health losses and contribute to the complex decision-making process.OBJECTIVE This study estimates the cost of schistosomiasis in Brazil in 2015.METHODS We conducted a cost of illness study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
(20 reference statements)
0
26
0
4
Order By: Relevance
“…Primeiramente, essa parasitose é mais incapacitante que letal 3, 16 , reduzindo o número da população economicamente ativa. Além disso, a esquistossomose gera altos custos à saúde pública, divididos entre os custos diretos (diagnóstico e tratamento de complicações), custos diretos não relacionados à saúde (transporte e atendimento doméstico) e custos indiretos (auxílio doença e morte prematura) 17 . O turismo, por sua vez, também é afetado, visto que alguns pontos turísticos apresentam potencial risco de infecção 18 .…”
Section: Introductionunclassified
“…Primeiramente, essa parasitose é mais incapacitante que letal 3, 16 , reduzindo o número da população economicamente ativa. Além disso, a esquistossomose gera altos custos à saúde pública, divididos entre os custos diretos (diagnóstico e tratamento de complicações), custos diretos não relacionados à saúde (transporte e atendimento doméstico) e custos indiretos (auxílio doença e morte prematura) 17 . O turismo, por sua vez, também é afetado, visto que alguns pontos turísticos apresentam potencial risco de infecção 18 .…”
Section: Introductionunclassified
“…The fact that the significant distance in the Gi statistics is approximately 2 km allowed us to calibrate the surveillance activities to a concise and statistically pre-established area. Accordingly, it is possible to develop schistosomiasis control and monitoring activities at well-defined focal points, rationalizing the use of public resources, since Brazil spent approximately 7.7 million dollars in 2015 to control the infection 61 . Therefore, the information presented in this study as well as the tools used may be adequate to develop and direct surveillance actions that contribute to the control and even elimination of schistosomiasis in the municipality of Ourinhos.…”
Section: Discussionmentioning
confidence: 99%
“…However, susceptibility tests under laboratory conditions demonstrated that RBS was susceptible to the Puerto Rican strain of S. mansoni, reaching a positive detection rate of 4.17%, while BBS was resistant. Schistosomiasis is an infectious disease that affects 1.8 million people in Brazil, and most federal states of Brazil are affected by S. mansoni [29,30,31]. Previous studies have demonstrated that the intermediate host B. straminea plays an important role in the transmission of S. mansoni [32,33,34].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%